A point mutation c.473A > G of ITGB3 is responsible for the formation of the Wo(a) human platelet alloantigen - Holzwarth, Sarah T.; Strobel, Julian; Cooper, Nina; Leyh, Jörg; Bayat, Behnaz; Bein, Gregor; Zingsem, Juergen; Sachs, Ulrich J. (Transfusion, 2019)
CRIS-Team WoS Importer:2020-01-03

Detection of signature double-negative T cells is a predictive marker to identify autoimmune lymphoproliferative syndrome associated with FAS loss of function - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Dell'Orso, Gianluca; Aigner, Michael; Fecker, Gisela; Hinze, Claas; Wittkowski, Helmut; Bruns, Heiko; Zierk, Jakob; Metzler, Markus; et al. (American Journal of Hematology, 2024)
CRIS-Team Scopus Importer:2024-03-29

Detection of Signature Double-Negative T Cells Is a Reliable Marker for ALPS Associated with FAS Mutation - Eisenhauer, Nina; Miano, Maurizio; Naumann-Bartsch, Nora; Leyh, Jörg; Terranova, Paola; Hinze, Claas; Aigner, Michael; Wittkowski, Helmut; Bruns, Heiko; Ehl, Stephan; Metzler, Markus; Arkwright, Peter; et al. (BLOOD, 2022)
CRIS-Team WoS Importer:2023-03-17

Diagnostic evaluation of paediatric autoimmune lymphoproliferative immunodeficiencies (ALPID): a prospective cohort study - Hägele, Pauline; Staus, Paulina; Scheible, Raphael; Uhlmann, Annette; Heeg, Maximilian; Klemann, Christian; Maccari, Maria Elena; Ritterbusch, Henrike; Armstrong, Martin; Cutcutache, Ioana; Elliott, Katherine S.; von Bernuth, Horst; et al. (Lancet Haematology, 2024)
BACKGROUND: Lymphoproliferation and autoimmune cytopenias characterise autoimmune lymphoproliferative syndrome. Other conditions sharing these manifestations have been termed autoimmune lymphoproliferative syndrome-like diseases, although they are frequently more severe. The aim of this study was to define the genetic, clinical, and immunological features of these disorders to improve their diagnostic classification. METHODS: In this prospective cohort study, patients were referred to the Center for Chronic Immunodeficiency in Freiburg, Germany, between Jan 1, 2008 and March 5, 2022. We enrolled patients younger than 18 years with lymphoproliferation and autoimmune cytopenia, lymphoproliferation and at least one additional sign of an inborn error of immunity (SoIEI), bilineage autoimmune cytopenia, or autoimmune cytopenia and at least one additional SoIEI. Autoimmune lymphoproliferative syndrome biomarkers were determined in all patients. Sanger sequencing followed by in-depth genetic studies were recommended for patients with biomarkers indicative of autoimmune lymphoproliferative syndrome, while IEI panels, exome sequencing, or genome sequencing were recommended for patients without such biomarkers. Genetic analyses were done as decided by the treating physician. The study was registered on the German Clinical Trials Register, DRKS00011383, and is ongoing. FINDINGS: We recruited 431 children referred for autoimmune lymphoproliferative syndrome evaluation, of whom 236 (55%) were included on the basis of lymphoproliferation and autoimmune cytopenia, 148 (34%) on the basis of lymphoproliferation and another SoIEI, 33 (8%) on the basis of autoimmune bicytopenia, and 14 (3%) on the basis of autoimmune cytopenia and another SoIEI. Median age at diagnostic evaluation was 9·8 years (IQR 5·5-13·8), and the cohort comprised 279 (65%) boys and 152 (35%) girls. After biomarker and genetic assessments, autoimmune lymphoproliferative syndrome was diagnosed in 71 (16%) patients. Among the remaining 360 patients, 54 (15%) had mostly autosomal-dominant autoimmune lymphoproliferative immunodeficiencies (AD-ALPID), most commonly affecting JAK-STAT (26 patients), CTLA4-LRBA (14), PI3K (six), RAS (five), or NFκB (three) signalling. 19 (5%) patients had other IEIs, 17 (5%) had non-IEI diagnoses, 79 (22%) were unresolved despite extended genetics (ALPID-U), and 191 (53%) had insufficient genetic workup for diagnosis. 16 (10%) of 161 patients with a final diagnosis had somatic mutations. Alternative classification of patients fulfilling common variable immunodeficiency or Evans syndrome criteria did not increase the proportion of genetic diagnoses. INTERPRETATION: The ALPID phenotype defined in this study is enriched for patients with genetic diseases treatable with targeted therapies. The term ALPID might be useful to focus diagnostic and therapeutic efforts by triggering extended genetic analysis and consideration of targeted therapies, including in some children currently classified as having common variable immunodeficiency or Evans syndrome. FUNDING: Deutsche Forschungsgemeinschaft under Germany's Excellence Strategy. TRANSLATION: For the German translation of the abstract see Supplementary Materials section.
CRIS-Team Scopus Importer:2024-02-16

MAP2K1-MUTATED ECD/RDD-OVERLAP NON-LANGERHANS CELL HISTIOCYTOSIS RESPONDING TO COBIMETINIB - Classen, Carl Friedrich; Leyh, Jörg; Rümmele, Petra; Rosenwald, Andreas; Metzler, Markus (PEDIATRIC BLOOD & CANCER, 2021)
CRIS-Team WoS Importer:2020-12-18

Tolerability of Tumor Treating Fields in pediatric high-grade glioma patients illustrated by post-market surveillance data - Suchorska, B.; Lucaciu, R.; Jung, S.; Leyh, Jörg; Woelfl, M.; Hirt, C.; Scholz, M. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16